Kinerja ekspor gas dan hubungannya dengan investasi asing sektor gas di Indonesia - Rona Kaloka; Syamsurijal Tan; Heriberta Heriberta (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze the performance of gas exports and their relationship with foreign investment in the gas sector in Indonesia. The data used is time series data from 1995-2011. Data is sourced from the Investment Coordinating Board, Department of Energy and Mineral Resources, Bank Indonesia and the Central Statistics Agency. Data analysis using multiple linear regression and Pearson correlation. The results of the study found: 1) the average development of the value of Indonesian gas exports was 15.27 percent per year. The average contribution of gas exports to Indonesia's oil and gas exports is 45.69 percent per year. The average balance of trade of Indonesian gas products is US $ 8.07 billion. The role of gas exports on Indonesia's economic growth shows an average increase of 3.86 percent per year; 2) Factors that have a significant effect on Indonesia's gas exports are total domestic consumption, gas export prices and exchange rates. There is a negative relationship between the balance of trade of gas products and foreign investment in the gas sector. This means that if the balance of trade value of gas products increases, foreign investment in the gas sector will decline